Prosocial digital games for youth: A systematic review of interventions - Pamela Saleme (Elsevier, 2020)
Digital games aiming to improve children health behaviours have received increasing attention from scholars and practitioners due to their societal importance. However, there remains a very limited understanding on the scope, application and relevance of prosocial games on youth. This review systematically investigates the literature base of empirical examinations of prosocial digital game interventions for children and explores the measures applied and their effectiveness. According to PRISMA guidelines, a systematic literature search was performed using five academic databases (EBSCO, Ovid, ProQuest, Scopus and Web of Science). To assess risk of bias in the analysis of included studies Cochrane developed quality assessment framework RoB2 and ROBINS-I were applied. Eleven studies met the inclusion criteria. Discussion of the reviewed studies highlights a heterogeneity of measures and lack of a consistent framework, mixed but promising results, and implications of skills and attitudes impacting prosocial behaviours. Finally, it proposes an agenda for future research on prosocial digital games focused on implementing clear theoretical frameworks and analysing key game design attributes to enhance prosocial digital games’ effectiveness.